Efeitos da imobilização e remobilização por natação e salto em meio aquático sobre a morfologia da articulação talocrural e dos músculos sóleo e tibial anterior de ratos - Kunz, Regina Inês (2014)
Immobilization is a therapeutic modality that is used in the treatment of musculoskeletal disorders, which often cause tissue morphological changes, and which can be reversed by remobilization. This study examined the effects of immobilization and remobilization on morphological parameters of the ankle joint and the soleus and tibialis anterior muscles of Wistar rats. Eighteen male rats had their right hind limb immobilized for 15 days. They were divided into the following 3 groups: G1, simply immobilized; G2, remobilized freely for 14 days; and G3, remobilized by exercises in water, performed on alternate days with progression in terms of the time and number of exercises. The contralateral limb was used as control. After the experimental period, the ankle, right (immobilized/remobilized) and left (control) joints, and the soleus and tibialis anterior muscles were processed for analysis using light microscopy. For the analysis of the ankle, three fields of distinct interest were identified in the sagittal section as follows: P1, anterior articular extremity (near the phalanges); P2, middle region of the joint; P3, posterior articular extremity. Histomorphometry revealed no significant differences between the groups and members, control and imobilized/remobilized, in terms of the number of chondrocytes and the thickness of the articular cartilage of the tibia and the talus. The morphological analysis of G1 showed the most significant degenerative lesions in the talus, such as exposure of the subchondral bone, flocculation and cracks between the middle and anterior regions of the articular cartilage, as well as the synovial membrane. Remobilization by exercises in water showed positive effects on the recovery of the ankle joint, compared with free remobilization. In the muscles, immobilization produced significant changes in the morphometric parameters of the soleus; in the tibialis anterior it only caused a change in muscle mass. However, there were changes in the morphology of the tibialis anterior, which showed polymorphic fibers and necrosis, as well as changes in the connective tissue. Swimming, combined with jumping in water, increased the smallest diameter of the fiber of the soleus muscle. Both free remobilization, and remobilization using exercises, increased the mass and the length of the tibialis anterior muscle, as well as its morphology